Isolation and distinctiveness in the design of e-learning systems influence user preferences - Al-Samarraie, Hosam; Selim, Hassan; Teo, Timothy; Zaqout, Fahed (Taylor & Francis Group, 2016)
When faced with excessive detail in an online environment, typical users have difficulty processing all the elements of representation. This in turn creates cognitive overload, which narrows the user's focus to a few select items.In the context of e-learning, we translated this aspect as the learner's demand for a system that facilitates the retrieval of learning content – one in which the representation is easy to read and understand.We hypothesized that the representation of content in an e-learning system's design is an important antecedent for learner preferences.The aspects of isolation and distinctiveness were incorporated into the design of e-learning representation as an attempt to promote student cognition.Following its development, the model was empirically validated by conducting a survey of 300 university students. We found that isolation and distinctiveness in the design elements appeared to facilitate the ability of students to read and remember online learning content. This in turn was found to drive user preferences for using e-learning systems.The findings provide designers with managerial insights for enticing learners to continue using e-learning systems.